Efektivitas Manual Therapy dan Ultrasound Terhadap Peningkatan Fungsi Gerak Bahu Pada Kasus Nyeri Bahu Et Causa Bursitis Subacromialis Dengan Parameter SPADI di RSUD Muhammad Natsir - Az-Zahra, Fadhilah; Lufitos, Ronal; Djawas, Faizah Abdullah (UI Scholars Hub, 2023)
ABSTRACT: Adhesive Capsulitis is a disorder that occurs in the shoulder area in the form of inflammation of the joint capsule which causes a feeling of stiffness and pain. Glenohumeral joint mobilization with the Maitland mobilization technique is using passive mobilization with physiological oscillatory movements which can produce a stretching effect and release of adhesive on the ligament capsule in the shoulder so that the range of motion of the shoulder joint can be increased. Hold relax is an exercise therapy with the principle of reciprocal inhibition which aims to improve antagonistic pattern relaxation, and mobilization, and to reduce pain. In this technique stimulation occurs through maximum contraction of a number of motor units simultaneously and maximally so that there is a decrease in muscle tension around the joint to increase the range of motion of the shoulder joint. This paper aims to determine the decrease in the SPADI (shoulder pain disability index) score by administering glenohumeral joint glide mobilization and hold relax during ultrasound intervention in a 71-year-old female patient who was diagnosed with adhesive capjuangitis ec. bursitis subacromialis dextra. After six meetings there was a significant decrease in the SPADI score.